Roles of graphite oxide, clay and POSS during the combustion of polyamide 6 - Dasari, Aravind (2014)
Two contrasting approaches have been adopted in the current study to obtain environmental benign and superior flame retardant polymer nanocomposites. In the first approach, polyhedral oligomeric silsesquioxane (POSS) is incorporated as an additional filler in polyamide 6/clay nanocomposite to improve the homogeneity of the ‘physical’ barrier, since POSS transforms to a glassy material upon fire and enhances the coupling of silicate layers to each other. In the second approach, fire response of an intumescent system, polyamide 6/graphite oxide (GO), is compared to polyamide 6/clay systems. The intention of using GO as a flame retardant is to benefit from its layered structure (‘physical’ barrier mechanism) and intumescent/blowing effect (‘chemical’ mechanism). Considerable insight and physical knowledge on the roles of different fillers in the combustion process have been obtained, which would provide useful guidance for the development of a new generation of nanocomposites. Besides the obvious contrasting differences in the flame properties of different materials, the incorporation of various fillers, depending on their nature, has both advantages and disadvantages from the viewpoint of flame retardancy.